1995
DOI: 10.1006/dbio.1995.1018
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Distribution of Tetraploid Cells in Mouse Tetraploid ↔ Diploid Chimaeras

Abstract: Tetraploid mouse embryos were produced by electrofusion at the 2-cell stage, cultured overnight, and aggregated with normal diploid embryos to produce tetraploid<==>diploid (4n<==>2n) chimaeric conceptuses. At 7 1/2 days the 4n<==>2n chimaeras were usually smaller and developmentally retarded compared to control diploid<==>diploid chimaeras. At 12 1/2 days the 4n<==>2n chimaeras had heavier placentas but there was no significant difference in fetal size. Tetraploid cells showed a restricted tissue distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 0 publications
6
71
1
Order By: Relevance
“…Studies at E12.5 and E7.5 have revealed that 4n cells are not simply restricted to extraembryonic tissues but more specifically to trophectoderm and primitive endoderm derivatives (James et al 1995). We also demonstrated that, as a group, 4n 2n blastocysts show a statistically significant greater contribution of 4n cells to the mural trophectoderm than to the inner cell mass or polar trophectoderm .…”
Section: supporting
confidence: 52%
“…Studies at E12.5 and E7.5 have revealed that 4n cells are not simply restricted to extraembryonic tissues but more specifically to trophectoderm and primitive endoderm derivatives (James et al 1995). We also demonstrated that, as a group, 4n 2n blastocysts show a statistically significant greater contribution of 4n cells to the mural trophectoderm than to the inner cell mass or polar trophectoderm .…”
Section: supporting
confidence: 52%
“…1A). Under these circumstances, wild-type tetraploid cells contribute exclusively to the placenta, whereas diploid cells contribute primarily to the embryo proper, with some contribution to the labyrinth of the placenta (19). As reported previously, this strategy led us to recover several live and apparently normal Rb Ϫ/Ϫ embryos, at developmental stages where no Rb Ϫ/Ϫ embryos derived from natural matings can be recovered (15).…”
Section: Resultsmentioning
confidence: 75%
“…Tetraploid cells are severely limited in their ability to contribute to embryonic tissues (31,32) and therefore contribute primarily to the placenta, whereas diploid cells in aggregates contribute primarily to the embryo proper (31,33). Here, tetraploid embryos were derived from matings between wild-type mice, and these were aggregated with diploid embryos derived from matings between Fatp4 ϩ/Ϫ mice, of which 1 ⁄ 4 are expected to be Fatp4 Ϫ/Ϫ embryos.…”
Section: Restoration Of Fatp4mentioning
confidence: 99%